Executive and visuo-motor function in adolescents and adults with autism spectrum disorder - Sachse, M.; Schlitt, S.; Hainz, D.; Ciaramidaro, A.; Schirman, S.; Walter, H.; Poustka, F.; Bölte, Sven; Freitag, C. (Springer New York LLC, 2013)
This study broadly examines executive (EF) and visuo-motor function in 30 adolescent and adult individuals with high-functioning autism spectrum disorder (ASD) in comparison to 28 controls matched for age, gender, and IQ. ASD individuals showed impaired spatial working memory, whereas planning, cognitive flexibility, and inhibition were spared. Pure movement execution during visuo-motor information processing also was intact. In contrast, execution time of reading, naming, and of visuo-motor information processing tasks including a choice component was increased in the ASD group. Results of this study are in line with previous studies reporting only minimal EF difficulties in older individuals with ASD when assessed by computerized tasks. The finding of impaired visuo-motor information processing should be accounted for in further neuropsychological studies in ASD.